Itinerários de uma identidade territorial na invenção do ser tocantinense - Brito, Eliseu Pereira de (2016)
This thesis has as its central theme the identity forged in the territorial relations, discussed under the bias of Human Geography. Territory and identity were analyzed in order to seek answers to the central research problem on the existence of a “territorial tocantinense identity”. This study aimed to analyze the constitution of territorial identity in the interface with territory formation as identification and differentiation of/in the spaces by multiple tocantinenses subjects. The approach proposed in the thesis is a qualitative study, using primary and secondary sources, interviews, historical documents and census information. We used techniques from Diagnóstico Rural Participativo – DRP for data collection through interviews and description of Tocantins’ landscapes in fieldwork. Such data were read by means of discourse analysis based on Nogueira (2001), and the territory was interpreted with basis on geosymbolism proposed by Bonnemaison (1987). It was considered that the first rupture of the territory of Goiás was in 1736, and it was the main framework of the territorial differentiation process. Ruptures in 1809 and 1821 were the result of a non-unified goiana identity. The subjects of the north of Goiás started to be called the nortenses by those from the south, who, in turn, were called the goianos. The territorial singularities created in the midst of a different world in the north of Goiás intensified over the XIX and XX centuries, and in 1956, under the Feliciano Braga command in Porto Nacional, the nortenses became the tocantinenses, which resulted in the creation of the state of Tocantins, in 1988. The mobility through the territory, the paths, places of work and leisure had their importance identified within in the formation of Tocantins’ territorial identity. Therefore, the Tocantins territorial identity is multiple and open to new territorial content, which forms a diachrony in the process. But also, there is a temporal duration of the identity process, which we identified as a persistence